The Landscape of Women's Health Podcasts: A Scoping Review - Ellen Beatriz Saboia de Castro; Janielle Ferreira de Brito Lima; Kayo Elmano Costa da Ponte Galvão; Eremita Val Rafael; William Caracas Moreira; Roger Rodrigues da Silva; Mônica Oliveira Batista Oriá; Maria Luziene de Sousa Gomes (Journal of Obstetrics and Gynaecology Research, 2026)
ABSTRACT Aim To map and characterize the available evidence on podcasts addressing topics related to women's health. Methods This scoping review was conducted in accordance with the Joanna Briggs Institute (JBI) guidelines. A comprehensive search was carried out in 12 databases in November 2025. Quantitative and qualitative studies addressing podcasts related to women's health were included, with no restrictions on publication date or language. The review protocol was registered on the Open Science Framework ( https://osf.io/7p9yr/overview ). The results are reported in accordance with the PRISMA extension for Scoping Reviews (PRISMA‐ScR). Results A total of 37 studies were included, primarily targeting health professionals and students ( n = 15). Thematic analysis showed that gynecology was the most frequent category (48.6%), with subthemes focusing on the climacteric ( n = 6), breast cancer ( n = 4), and fertility ( n = 3). Breastfeeding and healthy lifestyle shared second place (18.9% each), emphasizing lactation challenges and physical activity/nutrition, respectively. Obstetrics (13.5%) addressed labor and postpartum recovery, while motherhood (8.1%) explored maternal guilt. Finally, miscellaneous themes (16.2%) covered mental health, chronic diseases, and maternal mortality. Conclusion Podcasts have emerged as a versatile and strategic tool for health education and self‐care promotion throughout the female life cycle. While widely used for professional training and patient empowerment, there is a critical need for rigorous content curation and evidence‐based production to mitigate the risks of misinformation. Future research should focus on validating these digital tools and evaluating their long‐term impact on clinical outcomes and health literacy.